Tipe Kepribadian dan Pembelajaran Bahasa Perspektif Psikolinguistik pada Santri Pesantren Modern - Fauziah, Erna; Maulana, Fikri (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2022)
One of the distinguishing characteristics of modern Islamic boarding schools (pondok pesantren) is the use of language. Most elements within modern pesantren use Arabic and English as a means to respond to the challenges of the times, aiming to shape students (santri) into lifelong learners who are also capable of guiding society using various languages effectively and appropriately. Each student possesses a unique personality type, whether introverted or extroverted, which can either support or hinder the success of their learning process. The ability of modern pesantren and their students to recognize and utilize personality types in the learning process serves as a reference for every component to continue innovating sustainable methods and approaches that align with the students’ personality types in modern Islamic boarding schools